(untitled) (SASI, 2026)
Introduction: The Customary Dispute Resolution Mechanism (CDRM) of the Tolaki people in Southeast Sulawesi faces faces structural pressures arising from state legal expansion, jurisdictional overlap with formal courts, and the gradual reconfiguration of customary authority within Indonesia’s plural legal order. Historically, the Tolaki customary law system has played a central role in maintaining social harmony and resolving internal conflicts. However, the penetration of national law, globalization, and rapid socio-economic structural changes have placed Tolaki CDRM at a crossroads of adaptation. Purposes of the Research: This study aims to analyze the transformation patterns of Tolaki CDRM and to measure its resilience as an alternative dispute resolution mechanism amid the dominance of the national legal system. Methods of the Research: This qualitative research employs a socio-legal approach, combining normative analysis of Tolaki customary norms with empirical data from in-depth interviews with customary leaders (Pu’utobu, Mosoro), disputing parties, and judicial apparatus. Data was collected through document studies and field research in several Tolaki regions in Southeast Sulawesi. Results of the Research: (1) Tolaki CDRM has undergone significant institutional transformation through formalization under local regulations, (2) Procedural adaptations include standardized mediation and documentation systems such as structured mediation stages, written settlement documentation, and administrative reporting mechanisms; (3) CDRM demonstrates high resilience, sustained by the philosophical foundation of Kalo Sara and dual legitimacy—traditional community-based legitimacy and administrative state recognition. CDRM operates in active co-existence with the national legal system, often functioning as a pre-litigation mechanism. The restorative justice approach of CDRM, emphasizing social relationship recovery (Loleka), proves more effective than retributive formal justice in maintaining long-term kinship harmony.